Supply chain management : a global perspective - Sanders, Nada R. (Hoboken, NJ : John Wiley & Sons, 2012)
'Existing supply chain management books focus on logistics, operations management, and purchasing. Sanders provides supply chain managers with a completely unique approach, presenting SCM from a balanced, integrative, and business-oriented viewpoint. Rather than examining SCM as an offshoot of other business functions, this book discusses it as a boundary-spanning function that is intertwined with other organizational functions. It contains extensive pedagogy and solved problems to make difficult concepts easy to understand. A rich set of current examples are also included to make the material more relevant. Supply chain managers will finally have a resource that takes the business perspective'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Business logistics